Digit ratio as a predictor of cardiovascular endurance and speed performance among children / Izyana Najihah Ismail - Ismail, Izyana Najihah (Faculty of Sport Science and Recreation, 2015)
The ratio between 2D (index finger) and 4D (ring finger) has produced much enthusiasm among specialist. Previous research shows that men tend to have low digit ratio than women. It showed that 2D:4D, a putative correlate of prenatal testosterone, has been found to relate performance in sports and athletic which is low 2D:4D that have high prenatal testosterone correlate with high performance. Nowadays, the student of children's achievement in sports has now become important factors of identifying sporting athletic ability at early ages of child development. The objective of this study is to investigate the relationship between low digit ratio and high digit ratio towards cardiovascular endurance and speed among children. This study was used purposive sampling technique by examining the digit ratio of male and female children aged 11.13±0.82 years (n=40) by putting them through physical fitness measures to examine the relationship of the digit ratio with performance in the tests. 20 meter shuttle run test and 50 meter sprint test were conducted. This study finds the strong relationship between low digit ratio towards cardiovascular endurance, which is 2.95±0.52, p = .001 and speed performance which is, 9.33±0.97, p = .001 rather than high digit ratio. The results present more opportunities to be explored in talent identification, especially in the youth, establishing the value of using the 2D:4D ratio as part of the process of identifying sporting ability